(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Artificial Intelligence (AI) has emerged as a transformative force across industries, notably revolutionizing agriculture and food systems. AI techniques such as machine learning, computer vision, and natural language processing are redefining how food is produced, processed, distributed, and consumed. This paper provides an in-depth analysis of AI’s applications along the food value chain, examining recent technological innovations, strategic benefits, and the challenges they pose. Tables and figures illustrate key trends, while a discussion of ethical and regulatory considerations highlights the need for responsible implementation. The study concludes that AI holds immense promise for improving sustainability, productivity, and personalization in the food sector, provided stakeholders navigate ethical and infrastructural barriers with care.